Comparison of Giant-Slalom Results, Selected Anthropometric Measurements and Physical Fitness Tests between Female and Male Competitors in Under 14 Category - Stojan Puhalj (University of Maribor Press, 2016)
The purpose of the research was to determine whether there are any differences in selected anthropometric measurements, physical fitness tests and the average times achieved in three competitions in giant slalom between female and male alpine skiing competitors in category U14. The research was conducted on a sample of 40 categorized competitors, 20 boys M = 12.5; SD = 0.513 and 20 girls M = 12.55; SD = 0.510. Gender differences in selected anthropometric measurements (volume of the left knee, body mass index (BMI), and percentage of body fat), selected physical fitness tests (ten jumps on both legs, running eights, and test of stability), and ski result were assessed using t-test for independent samples. In order to assess ski result, average time from tree giant-slalom runs was used. Statistical significance was set at the α level of 0.05. The results showed that there were statistically significant differences (p <0.05) only in the percentage of body fat. We established that the levels of selected physical fitness tests in the female and male competitors aged under 14 years in the season 2013/14 are equal. It should also be noted that the groups do not differ in most of the selected anthropometric dimensions. It is therefore not surprising that the level of skiing skills, gained by female and male competitors in categoriesU14, is equal. The research results demonstrated the possibility of uniform and related training procedures and competitions in alpine skiing for boys and girls aged under 14 years.